2022
DOI: 10.1186/s40104-022-00703-5
|View full text |Cite
|
Sign up to set email alerts
|

Trace amounts of antibiotic altered metabolomic and microbial profiles of weaned pigs infected with a pathogenic E. coli

Abstract: Background Our previous study has shown that supplementation of trace amounts of antibiotic exacerbated the detrimental effects of enterotoxigenic E. coli (ETEC) infection and delayed the recovery of pigs that may be associated with modified metabolites and metabolic pathways. Therefore, the objective of this study was to explore the impacts of trace levels of antibiotic (carbadox) on host metabolic profiles and colon microbiota of weaned pigs experimentally infected with ETEC F18. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
3
4
0
Order By: Relevance
“…S 2 ). This observation is consistent with our previous research [ 35 ] and research published by other labs [ 36 , 37 ]. These alterations suggest that antibiotic treatment may increase amino acid availability for the host.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…S 2 ). This observation is consistent with our previous research [ 35 ] and research published by other labs [ 36 , 37 ]. These alterations suggest that antibiotic treatment may increase amino acid availability for the host.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, S. suis is capable of invading multiple organs to cause exaggerated inflammation, which has to be treated with antibiotics [ 71 ]. The reduced abundance of Streptococcaceae in colon digesta of pigs was also observed in our previous experiment when carbadox was administered [ 35 ].…”
Section: Discussionsupporting
confidence: 72%
“…It is worth noting that only 11 metabolites were identified in the present study. Similar results were also obtained by He et al [ 8 ] and Kim et al [ 35 ], who found that only small subsets of metabolites were found to be differentially expressed between E. coli F18 challenged pigs and non-challenged pigs (serum, ileal mucosa and colon digest). These findings indicated that the relatively stable metabolic profile may be a global characteristic for ETEC infection, which presents the demand for a more efficient approach to discover metabolic biomarkers rather than classic statistical methods, such as the machine-learning approach.…”
Section: Discussionsupporting
confidence: 88%
“…Kim et al . [ 49 ] found that cabadox concentration was the highest on day 5 in the serum and colon microbiota. Another experiment conducted with manure samples confirmed that the maximum excretion of difloxacin and sarafloxacin occurred on days 4−6 after oral administration [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sequentially injected enrofloxacin on days 2−3 causes high concentrations of antibiotics in bloodstream as well as in the excretory system. Kim et al [49] found that cabadox concentration was the highest on day 5 in the serum and colon microbiota. Another experiment conducted Available at www.veterinaryworld.org/Vol.16/January-2023/25.pdf with manure samples confirmed that the maximum excretion of difloxacin and sarafloxacin occurred on days 4−6 after oral administration [50].…”
Section: Enrofloxacin Determination In the Collected Pig Urinementioning
confidence: 99%